2017
DOI: 10.1016/j.jsps.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, molecular modeling and anticancer activity of new coumarin containing compounds

Abstract: A series of new coumarin containing compounds were synthesized from 4-bromomethylcoumarin derivatives and different heteroaromatic systems methylene thiolinker. Twenty-four compounds were screened biologically against two human tumor cell lines, breast carcinoma MCF-7 and hepatocellular carcinoma HePG-2, at the national cancer institute, Cairo, Egypt using 5-fluorouracil as standard drug. Compounds hh and showed strong activity against both MCF-7 and HepG-2 cell lines with being compound is the most active wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…Geometric optimization for 3-D compounds was performed using Hyperchem release 8.0.7. hypercube Inc. The methodology used for docking was in accordance with the literature [49,50].…”
Section: Molecular Docking Methodologymentioning
confidence: 99%
“…Geometric optimization for 3-D compounds was performed using Hyperchem release 8.0.7. hypercube Inc. The methodology used for docking was in accordance with the literature [49,50].…”
Section: Molecular Docking Methodologymentioning
confidence: 99%
“…Coumarin's reduction of melanoma recurrence and inhibition of renal-cell carcinoma did not withstand corroborating trials [37]. Coumarin has dose dependent cytotoxicity against the Hep2 cell line [39]. Carbon-4 substituted coumarins are antiproliferative against breast and liver carcinomas [39].…”
Section: Phenolsmentioning
confidence: 98%
“…Coumarin has dose dependent cytotoxicity against the Hep2 cell line [39]. Carbon-4 substituted coumarins are antiproliferative against breast and liver carcinomas [39]. Carbon-4 substituted coumarins inhibit aromatase, protein kinase, quinone reductase induction, sulphatase, 17β-HSD3, Cdc25, DNA intercalation, HDACs, Hsp90, microtubulin, NF-κβ, and TNF-α [40].…”
Section: Phenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vincristine (Figure 4) is used for the treatment of acute lymphoblastic leukaemia and both Hodgkin's and-non-Hodgkin's lymphoma. 12 Scheme 8 Shows the synthetic steps of amino chloropyrano oxazine compounds and the graphical results showing the effects of these compounds on different types of cancer cells. The development in heterocyclic compounds its utility and applications toward cancer screening studies showed a lot of works in this area of drug discovery as an examples coumarin and oxazine compounds.…”
Section: Heterocyclic Compounds In Anti-cancer Drug Design Strategymentioning
confidence: 99%